2002
DOI: 10.1523/jneurosci.22-18-07850.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Replacement Therapy Reverses Abnormal Synchronization of Pallidal Neurons in the 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine Primate Model of Parkinsonism

Abstract: Previous physiological studies have revealed changes in firing rates and synchronization of pallidal neurons in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) primate model of Parkinson's disease. Several primate and human studies have demonstrated that dopamine replacement therapy (DRT) reverses the changes in the pallidal firing rates; however, the effects of DRT on pallidal synchronization have never been explored. To do so, we recorded the simultaneous activity of pallidal neurons of a vervet monk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
134
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 32 publications
17
134
1
Order By: Relevance
“…Our previous studies of simultaneously recorded cells indicated that, in the normal monkey, the activity of pallidal neurons is uncorrelated (Nini et al, 1995;Heimer et al, 2002). These results were presented as supporting the hypothesis of the parallel (vs funneling) organization of the basal ganglia circuitry (Bergman et al, 1998).…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…Our previous studies of simultaneously recorded cells indicated that, in the normal monkey, the activity of pallidal neurons is uncorrelated (Nini et al, 1995;Heimer et al, 2002). These results were presented as supporting the hypothesis of the parallel (vs funneling) organization of the basal ganglia circuitry (Bergman et al, 1998).…”
Section: Introductionsupporting
confidence: 65%
“…2). However, these cross-correlograms are very different from the flat crosscorrelograms typical of pallidal pairs recorded by different electrodes (Nini et al, 1995;Heimer et al, 2002). The correlation of neighboring neurons has multiple stereotypic phases: a decreased correlation around time 0 followed by an increase to higher than mean correlations on the time scale of the refractory period of the cells.…”
Section: Autocorrelations and Cross-correlations Of Pallidal Neuronsmentioning
confidence: 78%
See 2 more Smart Citations
“…The finding of increased cross-correlation of single-cell discharge in many basal ganglia regions in animal models and patients with PD and increased LFP amplitudes in specific power spectral ranges indicates that the normal level of independence of discharge is substantially reduced in the parkinsonian state [44,322,323,325,326]. Effective antiparkinsonian therapies, including levodopa replacement and DBS reduce the LFP amplitudes to more normal levels, and reduce the abnormal synchrony of neurons in at least some brain regions [see, e.g., 152,297,327].…”
Section: Abnormal Levels Of Synchrony May Be a Fundamental Electrophymentioning
confidence: 99%